(untitled) (Journal of the College of Basic Education, 2026)
This research aims to study the spatial distribution of dental prosthetic laboratories in Baghdad/Al-Rusafa district and to identify their distribution trends and patterns, represented by (nearest neighbor coefficient, mean geographic center, central phenomenon, standard distance, distribution direction, and allocation range), through the use of statistical analysis and Geographic Information Systems (GIS) ,The research concluded that the distribution pattern of dental prosthetic laboratories in Baghdad/Al-Rusafa district is a closely spaced random distribution, and that the spatial distribution direction of the laboratories in the study area is (west-northeast and east-southeast).